The Effect of Composites Containing Daluga on Blood Glucose Levels of White Rats (Rattus norvegicus) - Esrah Anna Adeleid Agimat; Livana Dethris Rawung; Emma Mauren Moko; Iriani Setyawati; Helen Joan Lawalata; Dino Rahardiyan (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Blood glucose is a term that refers to the glucose level in the blood. The food type and physiological functions of the body can increase blood glucose. The right food can maintain stable blood sugar. One food source that can maintain stable blood sugar is tubers. One of them is daluga tubers which have a low glycemic index value. This study aims to determine the effect of giving composites made from daluga tubers for 42 days on the blood glucose levels of white rats (Rattus norvegicus). This study used a completely randomized experimental design with nine treatments and three replications. An experimental animal was given 30 g of food each day for 42 days based on the group of treatments. The drinking water was given ad libitum. Blood glucose was measured on days 21 and 42. The results showed that providing daluga-based composite feed to mice affected blood glucose levels (p<0.05). The feeding treatment was 100% composite 3 consisting of 30% daluga flour, 40% rice flour, and 30% corn flour, a daluga-based food can potentially be a food ingredient that can maintain stable blood glucose levels. So it can be concluded that composite 3 could be safe to consume by the diabetes patient.